The role of manager compensation and integrated reporting in company value: Indonesia vs. Singapore - St. Dwiarso Utomo; Zaky Machmuddah; Dian Indriana Hapsari (Economies, 2021)
The disclosure of integrated reporting elements can reduce information asymmetry for investors when valuing a company. This study aimed to empirically evaluate the effect of manager compensation, directly or indirectly, on firm value, through the mediating role of the disclosure of integrated reporting elements. The research sample included manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the Singapore Stock Exchange (SGX). The method of analysis was PLS-SEM, using the WarpPLS 7.0 application. The results showed that compensation significantly affects firm value and the disclosure of integrated reporting elements. Integrated reporting has a significant positive impact on firm value. In addition, the disclosure of integrated reporting can mediate the impact of manager compensation on increasing firm value. This research theoretically supports agency theory, disclosure theory, and signal theory, although it is not fully applicable to each country or region of the sample company. The current research contributes to the understanding of the importance of a company's integrated reporting disclosure in improving company value among investors. Integrated reporting describes how a company creates value over time. Our results also suggest that regulators should oblige public companies to disclose integrated reporting.
Keywords: 330; information asymmetry; compensation; firm value; integrated reporting